EFL STUDENTS' MASTERY OF ENGLISH SUFFIXES - Nuralizah Nuralizah; Ardiana Ardiana (Institut Agama Islam Negeri Bone, 2025)
The This study aimed to assess students' proficiency in using derivational suffixes, focusing on their ability to apply four types of suffixes through the online platform Google Forms. A quantitative descriptive approach was employed, with a sample of 38 fifth-semester English education students from Muhammadiyah University of Makassar. Data were collected using multiple-choice tests and analyzed by calculating total scores, percentages, and average proficiency levels. The findings revealed that 10.53% of students achieved 'Excellent' and 'Very Good' proficiency, while 23.68% were classified as 'Good'. Additionally, 7.89% fell into the 'Fairly Good' and 'Fair' categories. However, 28.95% of students were in the 'Poor' category, and 10.53% were classified as 'Very Poor'. Further analysis showed that students demonstrated the highest competence in verb suffixes, with an average score of 66.45%, followed by adverbial suffixes at 55%, adjective suffixes at 26%, verb suffixes at 10%, and noun suffixes at 9%. These results indicate that overall proficiency in suffix usage among fifth-semester students remains relatively low, highlighting the need for targeted instructional strategies to improve their understanding and application of derivational suffixes.